Analysis of heavy metals concentration in sediments and water samples of selected functional dams in Oyo State, Southwestern Nigeria (2008)
"The quality as well as the quantity of clean water supply is of vital significance to the welfare of mankind particularly in the developing countries. Therefore, knowing the concentration of heavy metals present in Dams can help us to ascertain the health safety of the populace using the water for drinking and domestic purposes. Ten Dams at Oyo State in the Southwestern Nigeria were studied for the heavy metals concentration contained in the sediments and water of the selected Dams. Bottom sediments and water were collected from the selected dams for analysis. Analysis of both the water and sediments to determine the concentration of each heavy metal was evaluated. The result obtained shows that, the concentration of Manganese (Mn) ranges from 14.8 mg/kg to 332.96 mg/kg followed by Zinc (Zn) which ranges between 6.18 mg/kg and 52.53 mg/kg which spread across all locations., Lead (Pb) was not detected in virtually all the locations except in Ilora which has a concentration of 0.87 mg/kg and this may be as a result of the activities of motor mechanics and vulcanizers around the dam. In the water samples, the result showed that the concentration of heavy metals is very low which is far below the limit specified by World Health Organization (WHO). Zn has the highest concentration ranging from 0.049mg/kg to 0.729mg/kg, followed by Mn which has concentration between 0.011mg/kg and 0.344mg/kg. Pb, Cadmium (Cd) and Cobalt (Co) were not detected at all in all the water samples. The variation in the concentrations may be due to geological nature of the ground, solubility, an ion exchange and human activities. "